Correlation of excess volumes of mixing of liquids by means of the Clausius equation of state - Hamam, S. E. M.; Elshayal, I. M.; Lu, B. C. Y. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The Clausius equation of state was modified in two ways for calculating excess volumes of mixing (VE) of liquids. In one modification, the three parameters of the equation were made temperature dependent and were calculated from vapor pressure and saturated liquid and vapor densities of the pure component. In another modification, one of the parameters â„¦c, of the equation was treated as temperature independent and was assigned a value given by the original equation, while the other two parameters were considered temperature dependent and were determined from vapor pressure and saturated liquid density of the pure component. The Clausius equation was then used with appropriate mixing parameters to calculate VE. The results obtained compared well with the available data, although the shapes of VE vs x curves are somewhat different. The systems studied include nitrogen-argon, nitrogen-oxygen, argon-oxygen, benzene-hexane and benzene-toluene.